1997
DOI: 10.1111/j.1445-2197.1997.tb01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Impact of Pneumoperitoneum on Intraperitoneal Implantation and Growth of Tumour Cell Suspension in an Experimental Model

Abstract: Background: An investigation of the effect of laparoscopy and CO2 pneumoperitoneum on the pattern of tumour implantation and growth in the peritoneal cavity was carried out. Methods: A suspension of viable adenocarcinoma cells was introduced into the left upper quadrant of the peritoneal cavity of 36 syngeneic immune‐competent rats at laparotomy, laparoscopy with CO2 insufflation, and gasless laparoscopy (12 rats in each group). Six days later the peritoneal cavity and surgical wounds were examined for macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 15 publications
0
72
0
Order By: Relevance
“…Numerous experimental studies confirmed that CO 2 pneumoperitoneum alters the behavior of adult tumor cells derived from colon carcinoma, adenocarcinoma, and breast cancer [11,15,16]. The behavior of pediatric tumor cells has not been investigated in this respect in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous experimental studies confirmed that CO 2 pneumoperitoneum alters the behavior of adult tumor cells derived from colon carcinoma, adenocarcinoma, and breast cancer [11,15,16]. The behavior of pediatric tumor cells has not been investigated in this respect in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…Studies in adult tumors show an increase in tumor dissemination after CO 2 insufflation [15,16], whereas there were no signs of an effect in neuroblastoma [17]. This and other potential influences of MIS on tumor growth and metastases need to be addressed.…”
Section: Discussionmentioning
confidence: 96%
“…These investigations, however, do not report any data regarding host tumor interaction in the peritoneal cavity. Another common design flaw involves the intraperitoneal administration of neoplasms that do not reside in the peritoneal cavity, such as mammary carcinoma, or neuroblastoma [122][123][124]. Unfortunately, these transplanted tumors do not demonstrate the same tissue tropism, making data interpretation open to criticism.…”
Section: Effect Of Carbon Dioxide (Co 2 ) On Macrophage Functionmentioning
confidence: 96%